PERSEPSI APARATUR PEMERINTAH DESA TERHADAP DANA DESA DI KECAMATAN SELUMA BARAT KABUPATEN SELUMA - Soleh, Ahmad; Susanto, Feri; Susanti, Reka (JURNAL EKOMBIS REVIEW, 2017)
Ahmad Soleh, Feri Susanto, Reka Susanti; Perception of the village government's arapatur to the  village fund in Seluma Barat Sub-district of Seluma District. The perception of the village government apparatus will affect activities in the use of village funds. The purpose of this research is to know the perception of village government apparatus to village fund in Seluma Barat sub-district of Seluma district. Determination of samples in this study using Purposive sampling. The sample in this research are 36 people, namely the Village Head, Secretary, Treasurer, and the head of BPD who served as the village government apparatus from 9 (Nine) villages in Seluma Barat District Seluma  District. The nine villages include Talang Perapat village, Purbosari village, Air Latak village, Pagar Agung village, Talang Tinggi village, Lunjuk village, Sengkuang village, Tanjung Agung village and Lubuk Lagan village. Rating Scale is used in analyzing data obtained by using questionnaires. The results showed that the perception of the village government apparatus on village governance activities showed good interpretation (71.8%); Perceptions of village government apparatuses towards development activities and improvements in village infrastructure show excellent interpretation (88.6%); Perceptions of village government apparatuses on community empowerment activities showed excellent interpretation (85.4%); And perception of village government apparatus towards social activities showed excellent interpretation (81,2%).Key Words:  Perceptions of the Village Government Apparatus, Village Funds, Seluma Barat District, Seluma District